2020
DOI: 10.1001/jamanetworkopen.2019.20255
|View full text |Cite
|
Sign up to set email alerts
|

Association of Electronic Cigarette Regulations With Electronic Cigarette Use Among Adults in the United States

Abstract: IMPORTANCE Millions of Americans use electronic cigarettes (e-cigarettes). A growing number of state and local governments have started to draft and implement laws regarding the sale, marketing, and use of e-cigarettes. The association of US state regulations regarding e-cigarettes with e-cigarette use remains unknown. OBJECTIVE To examine the association of US state regulations regarding e-cigarettes with current e-cigarette use among adults in the United States. DESIGN, SETTING, AND PARTICIPANTS This cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Studies of young adults demonstrate that the convenience, discreetness, and similarity of e-cigarettes to cigarettes serve as both motives for use and barriers to quitting vaping [ 20 , 21 , 22 ]. Although smoke-free air laws have been shown to reduce cigarette smoking rates [ 23 ], state laws prohibiting e-cigarette use indoors have not been shown to be associated with reductions in e-cigarette use among young adults [ 24 ], suggesting that other intervention strategies may be needed to reduce e-cigarette use in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of young adults demonstrate that the convenience, discreetness, and similarity of e-cigarettes to cigarettes serve as both motives for use and barriers to quitting vaping [ 20 , 21 , 22 ]. Although smoke-free air laws have been shown to reduce cigarette smoking rates [ 23 ], state laws prohibiting e-cigarette use indoors have not been shown to be associated with reductions in e-cigarette use among young adults [ 24 ], suggesting that other intervention strategies may be needed to reduce e-cigarette use in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Considering potential health risks associated with e-cigarettes, to combat the epidemic of e-cigarette use, since 2010 several states and local governments started to implement laws restricting the sale, marketing, and use of e-cigarettes [ 44 ], which has been shown to be associated with reduced e-cigarette use among US adults [ 45 ]. More recently, the US Food and Drug Administration (FDA) implemented the flavor enforcement policy on February 6, 2020, which restricts the sale of all flavored, cartridge-based e-cigarettes except tobacco and menthol flavors [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The highest prevalence of active electronic cigarette users in the US in 2018 was among persons aged 18-24 years [ 3 ]. Among current smokers in one study, 24% reported e-cigarette use [ 36 ]; among current electronic cigarette users, 52% reported current conventional cigarette use while 19% denied prior cigarette use [ 45 ]. Smoking cessation, smoking reduction, and reduction in health risks are the most common reasons for the use of electronic cigarettes [ 36 ].…”
Section: Reviewmentioning
confidence: 99%